Beneficial co‐culture of jellyfish Rhopilema esculenta (Kishinouye) and sea cucumber Apostichopus japonicus (Selenka): implications for pelagic‐benthic coupling. Issue 2 (10th July 2012) - Ren, Yichao; Dong, Shuanglin; Wang, Xiubin; Gao, Qinfeng; Jiang, Senhao
Abstract This study investigated monthly changes of sedimentation and sediment properties in three different culture systems (ponds) – i.e. jellyfish Rhopilema esculenta monoculture (J), sea cucumber Apostichopus japonicus and jellyfish co‐culture (SJ) and sea cucumber monoculture (S) – to verify the feasibility of co‐culturing jellyfish and sea cucumbers. Results showed that jellyfish culture accelerated the settling velocity of total particulate matter (TPM). Average TPM settling velocities in the SJ (75.6 g m−2 day−1) and J (71.1 g m−2 day−1) ponds were significantly higher than that in the S pond (21.7 g m−2 day−1) from June to September during the jellyfish culture period. Average settling velocities of organic matter (OM), total organic carbon (TOC), total nitrogen (TN) and total phosphorus (TP) in the SJ pond increased significantly by 3.0, 2.9, 3.3 and 3.8 times, respectively, compared with those in the S pond. Sediment contents of OM, TOC, TN and TP in the SJ and J ponds were significantly higher than those in the S pond during the jellyfish culture season. The specific growth rate of sea cucumbers feeding on SJ sediment was significantly higher than that of those feeding on S sediment. Co‐culturing sea cucumbers with jellyfish may help alleviate benthic nutrient loading due to the jellyfish and provide a secondary cash crop.